2013
DOI: 10.1002/asia.201300240
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of 13‐Vertex Carboranes with Strong Bases: Synthesis and Structural Characterization of Carborane Monoanions with exo‐π Bonding

Abstract: Several monoanions of 13-vertex carboranes were prepared in high yields from the reactions of C,C'-linked 13-vertex carboranes with tBuOK or NaH in dry THF at room temperature. These monoanions were characterized by various spectroscopic methods, elemental analysis, and single-crystal X-ray diffraction. The results showed substantial double-bond character between the cage-carbon atom and the exo vicinal carbon atom, thus leading to charge delocalization into the cage. As a result, the atom-atom distances withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…The 1 H NMR spectrum of 13 displayed a triplet of the unique exo α-CH at 5.82 ppm with J = 4.8 Hz, indicative of the α-CH being split by its neighboring methylene unit. Accordingly, the 13 9 Elemental analyses also confirmed the composition of 13.…”
Section: Synthesismentioning
confidence: 56%
See 2 more Smart Citations
“…The 1 H NMR spectrum of 13 displayed a triplet of the unique exo α-CH at 5.82 ppm with J = 4.8 Hz, indicative of the α-CH being split by its neighboring methylene unit. Accordingly, the 13 9 Elemental analyses also confirmed the composition of 13.…”
Section: Synthesismentioning
confidence: 56%
“…We wondered whether such a salt is an intermediate for the formation of the final products 1-12. To this end, 11 9 it is suggested that the deprotonation of α-methylene in 13-vertex carboranes proceeds instantly after mixing with NHC to afford the imidazolium salt of carborane anion that is slowly converted to the final product 1.…”
Section: Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…15 It reacted with 1.5 equiv. of GeCl 2 •dioxane in refluxing THF for 3 days to give a single product according to the 11 16…”
Section: Synthesismentioning
confidence: 99%
“…[2][3][4][5][6] They have shown some interesting properties. [7][8][9][10][11][12] For example, they can be reduced by group 1 metals to form the corresponding nido-carborane dianions that are good π-ligands for d-block transition metals. Accordingly, several 14-and 15-vertex metallacarboranes of d-block transition metals have been synthesized using polyhedral expansion methodology.…”
Section: Introductionmentioning
confidence: 99%